2022-RA-678-ESGO CONTESSA/NEOCON-F trial: Assessing the effectiveness and safety of neoadjuvant chemotherapy followed by fertility-sparing surgery in FIGO 2018 stage IB2 cervical cancer. (20th October 2022) - Plante, Marie; van Trommel, Nienke E; Schaafsma, Mirte; Oza, Amit M; Rodriguez, Angela; Wang, Lisa; Sikorska, Karolina; Ferguson, Sarah E; Han, Kathy; Lheureux, Stephanie; Amant, Frédéric
Abstract : Introduction/Background: The optimal management of FIGO 2018 stage IB2 cervical cancer patients who desire to preserve fertility is unknown. Therefore, the CONTESSA/NEOCON-F trial (NCT04016389 ) aims to evaluate a promising, new fertility-sparing treatment: neoadjuvant chemotherapy (NACT) followed by fertility-sparing surgery (FSS). Methodology: This trial is an ongoing, phase II clinical trial, which will accrue 90 pre-menopausal, lymph-node negative, FIGO 2018 stage IB2 cervical cancer patients, aged between 18 and 40 years and who desire to preserve their fertility. All patients will receive three cycles of paclitaxel and platinum containing chemotherapy. Following NACT the response will be evaluated by clinical examination and MRI. Patients must achieve a complete or partial response (residual lesion <2 cm) to be eligible for FSS: a conisation or simple trachelectomy. Patients with suboptimal response (residual lesion ≥2 cm) will go off-study and receive definitive treatment, radical hysterectomy or chemoradiation as per local protocol. Patients will be followed for three years following FSS. The safety of this trial will be continuously monitored using Bayesian posterior probability and the stopping rule will be activated if there is at least 70% probability that two-year recurrence rate is above 10%. Results: The primary outcome is the rate of functional uterus defined as successful FSS and no need for adjuvant therapy post procedure. Secondary outcomes include the safety of the treatment, the response rate to NACT, and the recurrence-free and overall survival after two and three years. Finally, this trial will also explore the effect of NACT on ovarian function. Translational research will explore disease monitoring in blood plasma (HPV ctDNA) and cervical scrapes (DNA hypermethylation), and patients' quality of life will be assessed by questionnaires. Conclusion: The CONTESSA/NEOCON-F trial is opened for accrual in the Netherlands, Canada, and the United States. Currently, 10% of the target accrual has been reached.